AVALIAÇÃO EM EDUCAÇÃO DE INFÂNCIA: CONTRIBUIÇÕES DE TESES DE DOUTORAMENTO PORTUGUESAS - Lanes, Erone Hemann; Parente, Maria Cristina (Literatura em Debate, 2025)
The objective of this article is to analyze Portuguese scientific production on learning assessment in early childhood education, in order to identify contributions to Brazilian research. This is a qualitative state of knowledge. The bibliographic search was conducted in Portuguese Open Access Scientific Repositories using the descriptors ‘assessment of early childhood education’, ‘assessment of childhood learning’, ‘assessment of preschool learning’. Four theses were selected for analysis. The results indicated the relevance of the research to the corpus of theoretical references that address the topic in Brazil, mainly to understand the assessment, its models, approaches and concepts, and to plan appropriate practices for alternative and modern assessment. The absence of effective participation of children as part of the methodologies adopted by the theses stands out, an aspect considered as a significant way to qualify the assessment at this stage.